The “Spaghetti Project”: the final identification guide to European Terebellidae (sensu lato) (Annelida, Terebelliformia) - Lavesque, Nicolas; Hutchings, Pat; Londoño-Mesa, Mario H.; Nogueira, João M.M.; Daffe, Guillemine; Nygren, Arne; Blanchet, Hugues; Bonifácio, Paulo; Broudin, Caroline; Dauvin, Jean-Claude; Droual, Gabin; Gouillieux, Benoit; et al. (European Journal of Taxonomy, 2021)
This paper is the conclusion of the “Spaghetti Project” aiming to revise French species of Terebellidae sensu lato (s.l.) belonging to the five families: Polycirridae, Telothelepodidae, Terebellidae sensu stricto (s.s.), Thelepodidae and Trichobranchidae. During this project, 41 species were observed, 31 of them new for science: eight species of Polycirridae, eleven species of Terebellidae s.s., three species of Thelepodidae and nine species of Trichobranchidae. We provide a comprehensive key for all European species of terebellids with a focus on the important diagnostic characters for each family. Finally, we discuss issues on taxonomy, biodiversity and cryptic and pseudo-cryptic species of polychaetes in European waters, based on results obtained during this project.